(3GdeSFhdjI GdJCOjHjI dVHGW GdTQWI (B:s (3OQGSI ebGQfI (B/s - (3eMehO YHOGdefYe aGjRs; (3GdSjO Ndjd CMeO gjcds; (3LGeYI CSjhWs (3cdjI GdMbhbs ((3CSjhW(B:s (3cdjI GdMbhb(B-(3LGeYI CSjhW,s, 2004)
(3JWdY gPg GdOQGSI Gdi GHQGR GdJHGjf Hjf GdeSFhdjI GdJCOjHjI dVHGW GdTQWI ebGQfI HGdeSFhdjI GdJCOjHjI ddYGedjf GdeOfjjf hJhGab gPg GdbhGYO eY WHjYI GdCYeGd GdeSfOI dcd aFI hHGdJGdj CgOGa GdOQGSI ajeG jdj(B: (3Gdhbha Ydi CHYGO GdJCUjd GdJGQjNj dfXGej GdhXjaI GdYGeI hGdTQWI hGfYcGSGJgeG Ydi WHjYI GdeSFhdjI GdJCOjHjI HUaI YGeI hVHGW GdTQWI HUaI NGUI heQOhOGJ Pdc Ydi NUhUjI gPg GdeSFhdjI hbhGYOgG hechfGJgG GdeNJdaI hGSJdgGe GdadSaI GdJi JQJcR YdjgG bIGYO GdeSFhdjI GdJCOjHjI dVHGW GdTQWI ef NdGd HMK WHjYI GdYed GdTQWj hCbSGegG hGdSdWGJ GdeJYOOI GdJi jedcgG VHGW GdTQWI dBOGA QSGdJge hGgejI GdhXjaI GdTQWjI hGdWHjYI GdbGfhfjI dgjAI GdTQWI hHjGf eOi GJSGb bhGYO GdeSFhdjI GdJCOjHjI dVHGW GdTQWI hUdGMjGJgG hWQM QDi YdejI LOjOI cCaQGR dJMdjd echfGJ GdeSFhdjI GdJCOjHjI hbhGYOgG hJQTO ef CWQ JMOjO GdeSFhdjI GdJCOjHjI dVHGW GdTQWI hNGUI aj eLGdGJ GdJLQje hGdYbGH hGdSdWGJ GdJCOjHjI hJMbb YfUQi GdaGYdjI hGdVeGf GddGRejf dGSJbQGQ ChVGY gPg GdaFI hcaGdI GfJXGe GdYed HPdc GdeQab Gdeges
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI CSjhW, cdjI GdMbhb, bSe GdbGfhf GdYGe (B2004s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: (3UaMI (B1076-1107s
Keywords: (3VHGW GdTQWI s; (3GdJCOjH aj eLGd GdhXjaI GdYGeI hhXjaI GdTQWIs; (3adSaI GdeSFhdjI GdJCOjHjIs; (3TQYjI GdeSFhdjI GdJCOjHjIs; (3CMcGe GdeSFhdjI GdJCOjHjIs; (3GdYbhHI GdJCOjHjIs; (3GdeTQhY GdYGes -- (3LGeYI CSjhWs -- (3GdbGfhf GdYGes